2006
DOI: 10.1063/1.2221525
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between reliability of thermal oxides and dislocations in n-type 4H-SiC epitaxial wafers

Abstract: The correlation between thermal oxide reliability and dislocations in n-type 4H-SiC (0001) epitaxial wafers has been investigated. The thermal oxides were grown by dry oxidation at 1200°C followed by nitrogen postoxidation annealing. Charge-to-breakdown values of thermal oxides decrease with an increase in the number of the dislocations in a gate-oxide-forming area. Two types of dielectric breakdown modes, edge breakdown and dislocation-related breakdown, were confirmed by Nomarski microscopy. In addition, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 13 publications
1
66
2
Order By: Relevance
“…[4][5]. It has been reported that charge-to-breakdown values of thermal oxides decrease with an increase in the number of the dislocations.…”
Section: (F)mentioning
confidence: 96%
See 2 more Smart Citations
“…[4][5]. It has been reported that charge-to-breakdown values of thermal oxides decrease with an increase in the number of the dislocations.…”
Section: (F)mentioning
confidence: 96%
“…It has been reported that charge-to-breakdown values of thermal oxides decrease with an increase in the number of the dislocations. [4] Therefore, the dislocations observed in the bad unit may be the root cause for the early breakdown of the power MOS.…”
Section: (F)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reliability and premature BD generation mechanisms in thermal oxides grown on 3C-SiC has not been addressed. In addition to the intrinsic properties of the dielectric, the BD event is controlled by defects on the semiconductor surface, the conduction band offset at the semiconductor/SiO 2 interface, and oxidation and post oxidation conditions [3,5]. The nature of the defects, the conduction band offset and the optimal oxidation and post oxidation conditions [6] are different for 3C-SiC compared to the better studied 4H polytype.…”
Section: Impact Of Morphological Features On the Dielectric Breakdownmentioning
confidence: 97%
“…However, one of the key obstacles in SiC-based MOS devices is poor gate oxide reliability. It has been pointed out that the dielectric breakdown of SiO 2 on 4H-SiC(0001) substrates mainly occurs at basal plane dislocation in the epilayer during constant voltage time-dependent dielectric breakdown (TDDB) measurement [1]. Meanwhile, our conductive atomic force microscopy (C-AFM) study on a thermally grown SiO 2 /4H-SiC(0001) structure has clearly demonstrated that dielectric breakdown is preferentially induced at the step bunching [2].…”
mentioning
confidence: 96%